Collection and Transplantation of Peripheral Blood Stem Cells in Children: A Single-Center Experience - Cengiz Zeybek; Orhan Gürsel; Ahmet Bolat; İbrahim Eker; Erman Atas; Ahmet Emin Kürekçi (Genel Tıp Dergisi)

(untitled)
Background/Aims: As a source of hematopoietic stem cells, peripheral blood stem cells have been used more frequently in both malignant and non-malignant diseases. There are some difficulties in the collection of PBSC from children compared to adults such as vascular access and, extracorporeal circuit volume, especially in small children.Methods: In this study, we present our experience in 63 children who underwent peripheral blood stem cell collection and transplantation between November 2016 and September 2023. Results: The median age and weight of the children at the time of apheresis procedures were 10.25 years and 34 kg, respectively. Of 63 peripheral blood stem cell collection and transplantations, 48 were autologous and 15 were allogeneic. The median cell yield per apheresis procedure was 2.6 x 106 CD34+ cells/kg (0.6-9.66). Four of the total 63 patients and donors required multiple apheresis procedures. No significant side effects were observed after apheresis procedures. Conclusions: We observed that in experienced hands, peripheral blood stem cell collection and transplantation in children is at least as safe and effective as in adults.